TERAPI WELL-BEING UNTUK MENINGKATKAN PSYCHOLOGICAL WELL-BEING PADA REMAJA YANG TINGGAL DI PANTI SOSIAL BINA REMAJA X - Ivon Hartato; Debora Basaria; Soemiarti Patmodewo (Universitas Bunda Mulia, 2017)
The purpose of this research is to know the application of Well-Being Therapy (WBT) in increasing psychological well-being of adolescents who live in PSBR X. This research used pre-experimental one group pretest-posttest design, the score of psychological well-being from the participants will measured at the beginning and at the end of WBT, using Ryff psychological well-being scale. Participants of this research are two adolescents, 16 to 18 years old, and live in PSBR X within six months. WBT conducted in six sessions, about 60 minutes in each session. The result of the research showed that the psychological well-being of two participantsincreased after finished the WBT. This prove that WBT can increase psychological well-being of adolescents who live in PSBR X. Keywords: well-being therapy, psychological well-being, adolescents, social institution